Enamel microabrasion: an overview of clinical and scientific considerations - Pini, Nubia Inocencya Pavesi; Sundfeld Neto, Daniel; Aguiar, Flávio Henrique Baggio; Sundfeld, Renato Herman [UNESP]; Martins, Luis Roberto Marcondes; Lovadino, José Roberto; Lima, Debora Alves Nunes Leite (Baishideng Publishing Group, 2015)
Superficial stains and irregularities of the enamel are generally what prompt patients to seek dental intervention to improve their smile. These stains or defects may be due to hypoplasia, amelogenesis imperfecta, mineralized white spots, or fluorosis, for which enamel microabrasion is primarily indicated. Enamel microabrasion involves the use of acidic and abrasive agents, such as with 37% phosphoric acid and pumice or 6% hydrochloric acid and silica, applied to the altered enamel surface with mechanical pressure from a rubber cup coupled to a rotatory mandrel of a low-rotation micromotor. If necessary, this treatment can be safely combined with bleaching for better esthetic results. Recent studies show that microabrasion is a conservative treatment when the enamel wear is minimal and clinically imperceptible. The most important factor contributing to the success of enamel microabrasion is the depth of the defect, as deeper, opaque stains, such as those resulting from hypoplasia, cannot be resolved with microabrasion, and require a restorative approach. Surface enamel alterations that result from microabrasion, such as roughness and microhardness, are easily restored by saliva. Clinical studies support the efficacy and longevity of this safe and minimally invasive treatment. The present article presents the clinical and scientific aspects concerning the microabrasion technique, and discusses the indications for and effects of the treatment, including recent works describing microscopic and clinical evaluations.
Keywords: Dental bleaching; Enamel microabrasion; Enamel surface; Esthetic treatment; Fluorosis; Hypoplasia